Mampukah Ukuran Perusahan Memoderasi Hubungan Profitabilitas Dan Leverage Terhadap Penghindaran Pajak - Barry Truman Agustadana; Khomsiyah Khomsiyah (Politeknik Ganesha Medan, 2025)
Tax in the eyes of the state is an income that is used to finance government administration, but for companies tax is a burden that can affect the profits generated by the company. The existence of these differences in interests makes taxpayers able to avoid taxation (Alfaruqi et al., 2019). The opportunity for tax avoidance to occur is also caused by the Indonesian government adopting a self-assessment system in its tax collection system (Razif & Rasyidah, 2020). This research is an extension of research conducted by Bratakusuma (2021). The population in the research is companies in the primary consumer goods and non-primary consumer goods sectors listed on the IDX in 2020 - 2022, with a total of 192 sample companies. The sampling method used in the research is the purposive sampling method and SPSS will assist in processing the data. The results of this research show that profitability has a negative effect on tax avoidance and leverage has a positive effect on tax avoidance. Company size strengthens the positive influence between leverage on tax avoidance and company size strengthens the negative influence between profitability on tax avoidance.